Pengembangan Media Pembelajaran Fisika Berbasis STEM untuk Meningkatkan Kreativitas Siswa: Sebuah Tinjauan Literatur Sistematis - Tarigan, Fitri Kita Yulandari Br; Fadieny, Nurul; Safriana, Safriana (Universitas Garut, 2024)
The purpose of this study is to analyze the development of physics teaching tools using Science, Technology, Engineering and Mathematics (STEM) approach to enhance students' creativity. A qualitative approach was used to gain a deeper understanding of students' experiences with learning tools and their impact on creativity. This approach focuses on gathering information from relevant scientific papers between 2020 and 2024. These papers can be accessed in PDF format through Google Scholar using the Publish or Perish (PoP) application. A search of scientific papers using the keywords 'physics', 'STEM', and 'student creativity' yielded 200 journal articles. Based on the analysis, we conclude that the STEM approach provides a strong foundation for enhancing student creativity in the context of physics learning. This suggests that STEM not only effectively improves understanding and problem-solving skills, but also provides opportunities for students to think critically and find innovative solutions when learning physics.